1973
DOI: 10.1042/bj1350595
|View full text |Cite
|
Sign up to set email alerts
|

Affinity chromatography of nicotinamide–adenine dinucleotide-linked dehydrogenases on immobilized derivatives of the dinucleotide

Abstract: 1. Three established methods for immobilization of ligands through primary amino groups promoted little or no attachment of NAD(+) through the 6-amino group of the adenine residue. Two of these methods (coupling to CNBr-activated agarose and to carbodi-imide-activated carboxylated agarose derivatives) resulted instead in attachment predominantly through the ribosyl residues. Other immobilized derivatives were prepared by azolinkage of NAD(+) (probably through the 8 position of the adenine residue) to a number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
2

Year Published

1973
1973
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(55 citation statements)
references
References 24 publications
2
51
2
Order By: Relevance
“…Yeast alcohol dehydrogenase displays little affinity for either adsorbent, supporting the contention that this dehydrogenase may prefer 6-linked rather than derivatives linked through other positions [I 7, 291. ~-Glyceraldehyde-3-phosphate dehydrogenase is known to demonstrate a considerable degree of nonbiological adsorption on binding to a NAD + derivative linked through a hydrocarbon spacer arm [9,30] but that this could be alleviated by introduction of a more hydrophilic spacer arm [17]. Fig.4 (F) confirms these observations ; the enzyme interacts very weakly with the more hydrophobic adsorbent and is completely unretarded by the hydrophilic adsorbent.…”
Section: Affinity Chromatographysupporting
confidence: 77%
“…Yeast alcohol dehydrogenase displays little affinity for either adsorbent, supporting the contention that this dehydrogenase may prefer 6-linked rather than derivatives linked through other positions [I 7, 291. ~-Glyceraldehyde-3-phosphate dehydrogenase is known to demonstrate a considerable degree of nonbiological adsorption on binding to a NAD + derivative linked through a hydrocarbon spacer arm [9,30] but that this could be alleviated by introduction of a more hydrophilic spacer arm [17]. Fig.4 (F) confirms these observations ; the enzyme interacts very weakly with the more hydrophobic adsorbent and is completely unretarded by the hydrophilic adsorbent.…”
Section: Affinity Chromatographysupporting
confidence: 77%
“…It has been suggested that this strengthening is due to a 'compound affinity' effect in which the threshold salt concentration allows the operation of marginal non-biospecific interactions with the spacer arm which synergistically reinforce the weak bioaffinity to produce a relatively strong retardation, without being sufficient to cause any significant retardation on their own [8,9] .…”
Section: Resultsmentioning
confidence: 99%
“…When no more protein could be removed by the salt wash given, 2.1 mM Flaxedil (gallamine triethiodide) solution was used to achieve a bio-specific [9] elution of ACh.R. This eluent also displaced a small amount of other protein.…”
Section: Isolation Of Ac% R From Musclementioning
confidence: 99%
“…For muscles, quantitation and localisation of ACh.R, by exploitation of its essentially irreversible binding of labelled cu-bungarotoxin (BuTX), was initially described [3], and solubilisation of this ACh.R in detergents and some fractionation has been reported [4-71. Subsequently [S] , we reported upon a preparation, partly purified by affinity chromatography, of the form of ACh.R which is responsible for the extrajunctional ACh sensitivity of denervated mammalian muscle. We have further applied affinity chromatography in a more bio-specific form (in the sense in which this technique has been critically reviewed by Barry and O'Carra [9] ), and describe here the complete purification of this muscle ACh.R. [S] , as were materials not separately specified here.…”
Section: Introductionmentioning
confidence: 99%